High-dose rifampicin in tuberculosis: Experiences from a Dutch tuberculosis centre. - Charlotte Seijger (PLoS ONE, 2019)
Background Recent evidence suggests that higher rifampicin doses may improve tuberculosis (TB) treatment outcome. Methods In this observational cohort study we evaluated all TB patients who were treated with high-dose rifampicin (> 10 mg/kg daily) in our reference centre, from January 2008 to May 2018. Indications, achieved plasma rifampicin exposures, safety and tolerability were evaluated. Results Eighty-eight patients were included. The main indications were low plasma concentrations (64.7%) and severe illness (29.5%), including central nervous system TB. Adjusted rifampicin dosages ranged from 900 mg to a maximum of 2400 mg (corresponding to 32 mg/kg) per day. Patients with severe illness received high-dose rifampicin immediately, the others had a higher dosage guided by therapeutic drug monitoring. Four patients developed hepatotoxicity, of which two were proven due to isoniazid. Re-introduction of high-dose rifampicin was successful in all four. Eighty-seven patients tolerated high-dose rifampicin well throughout treatment. Only one patient required a dose reduction due to gastro-intestinal disturbance. Conclusion High-dose rifampicin, used in specific groups of patients in our clinical setting, is safe and well-tolerated for the whole treatment duration. Measurement of drug exposures could be used as a tool/guide to increase rifampicin dosage if a reduced medication absorption or a poor treatment outcome is suspected. We suggest to administer high-dose rifampicin to patients with severe manifestations of TB or low rifampicin exposure to improve treatment outcome.